Development of miniaturized control circuit of auto reclose earth leakage relay for a single phase 230V / Zulkifli Mat Yahya - Yahya, Zulkifli (2013)
Power distribution networks have been operated in an easy and simple unidirectional way. Many of electrical faults such as short circuit or over current and earth fault that occur are momentary in nature. The breaker disconnects the circuit whenever it detects unbalance current between the phase conductor and the neutral conductor. Such an unbalance is sometimes caused by current leakage through the body of a person who is grounded when accidentally touch the energized part of circuit. Normally the breaker that available in the market has to be reset manually when the fault occur and cannot differentiate between temporary fault and permanents fault. When the fault occurs in protected area, the protection system will force the breaker to trip. In order to turn the power back to normal operation, consumer needs to reconnect manually. One of the drawbacks of the common breaker is that, its cannot reconnect the power with the utility supply to normal operation condition although only a short disturbance occurs such as the lightning strike around the protected area. This paper presents the automatic reclosing circuit breaker which is a system that will be able to reconnect the system to the utility supply automatically without any human interference. The important of having automatic reclosing circuit breaker is to make power system self-sufficient. This system can be applied to single phase systems which are common systems that used in Malaysia. This circuit can be performed by application of an electronic control circuit (digital technology). The advantages of the system are reducing in consumer equipment's down time and maintenance time. This circuit consist of the electronic control circuit that used to reset the system. The general conclusion from this thesis work is that the circuit breaker will reconnect to the utility supply automatically when the breaker disconnects causes by the unbalance current.